중부내륙중심권 정부사업 공동 발굴 - 박시현 (한국농촌경제연구원, 2010)
The purpose of this research is to find linkages and collaboration projects between central inland regions of Korea, specifically the six counties of Yeongwol, Pyeongchang, Jecheon, Danyang, Yeongju and Bonghwa. These counties are looking for special projects that would allow them to receive support from the central government. This research mainly consists of three parts. Firstly, we studied the joint projects of the six counties. Based on that, we proposed basic directions and implementation strategies to promote oriental herbal medicine and tourism industries in the regions. Secondly, we proposed joint cooperation projects in conjunction with the individual counties. As county-specific projects, herbal medicine projects are proposed for Pyeongchang, Jecheon and Yeongju. A metal silicon industry project is proposed for Yeongwol as part of a renewable energy promotion project, a tourism project is proposed for Danyang endowed with beautiful scenery, and a forestry development project is proposed for Bonghwa. Finally, joint and individually specialized projects are presented to promote the central government's plan to support projects. The following measures are needed to develop and realize the suggested projects: (i) joint effort to be included in a super wider economic belt, (ii) joint effort to attract financial support from the central government, and (iii) joint effort to expedite the legislation of special laws assisting the limestone industry communities.